A STUDY APPROACH THROUGH SEGMENTATION BY USING ROUGHNESS INDEX AND MRI - Hussain, Mr. Athar; Raut, Anjali B (IJRDO -Journal of Computer Science Engineering, 2015)
The paper presents the color image segmentation based on rough-set approach has been proposed. The color image segmentation is one of the most challenging tasks particularly in the area of image analysis, computer vision, and pattern recognition. In this paper, the proposed algorithm based on roughness index to calculate the peaks and valleys values. Based on peak and valley values to achieve better segmentation, Experimental results shows the roughness index theory to achieve better color image segmentation results and shows the graphs of roughness measurement versus intensities and compare to histogram and histon techniques. We propose a color image segmentation approach based on rough set theory elements. Main contributions of the proposed approach are twofold. First, by using an adaptive threshold selection, the approach is automatically adjustable according to the image content. Second, a region-merging process, which takes into account both features and spatial relations of the resulting segments, lets us minimize over-segmentation issues. These two proposals allow our method to overcome some performance issues shown by previous rough set theory-based approaches.